Land or sea? Foraging area choice during breeding by an omnivorous gull - Isaksson, Natalie (Mov Ecol, 2016)
BACKGROUND: Generalist predators may vary their diet and use of habitat according to both internal state (e.g. breeding stage) and external (e.g. weather) factors. Lesser black-backed gulls Larus fuscus (Linnaeus 1758) are dietary generalists, foraging in both terrestrial and marine habitats during breeding. We investigate what affects the gulls’ propensity to forage at sea or on land. We assess the importance of terrestrial foraging to gulls in the Baltic Sea (sub. sp. L. f. fuscus), looking especially at their use of agricultural fields. RESULTS: Through the GPS tracking of 19 individuals across 3 years we tracked 1038 foraging trips and found that 21.2 % of foraging trips were predominantly terrestrial, 9.0 % were a mix of terrestrial and marine, and 68.5 % were exclusively marine. Terrestrial trips were (1) more frequent when departing around sunrise, whereas marine trips occurred throughout the day. Additionally, trips with mostly land-based foraging decreased as the breeding season progressed, suggesting dietary switching coincident with the onset of chick provisioning. (2) During cloudy and cold conditions terrestrial foraging trips were more likely. (3) We found no differences between sexes in their land-based foraging strategy. (4) Gull individuals showed great variation in foraging strategy. Using observations of agricultural fields, carried out for one year, we found that (5) gulls preferentially foraged on fields with short vegetation, and there was a positive association with occurrence of waders and other species of gulls. (6) The availability and use of these preferred fields decreased through the breeding period. CONCLUSIONS: This study found high prevalence of terrestrial foraging during early breeding as well as support for dietary switching early in the breeding season. The overall tendency for marine or terrestrial foraging was consistent within individuals, with gull identity accounting for much of the variation observed in foraging trips. Our results suggest that anthropogenic terrestrial food sources may play a role in the low breeding success of these gulls through either variation in quantity and/or quality. Finally, our study demonstrates the potential of combining data from GPS-tracking of individual animals with the ‘ground-truthing’ of habitat visited to elucidate the otherwise nebulous behavior of a generalist predator. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40462-016-0078-5) contains supplementary material, which is available to authorized users.